Strengthening and microbial regulation mechanism of Bacillus on purification device for grass carp culture wastewater - Li, Zhifei; Gao, Yan; Lu, Zhuoyin; Xie, Jun; Liu, Yang; Wang, Guangjun; Cheng, Xiangju (Frontiers in Environmental Science, 2023)
Aquaculture wastewater (AW) poses a threat to natural aquatic environments. Microecological agents are widely used to regulate and purify AW, with Bacillus being the most common. To evaluate the AW purification effect of adding Bacillus subtilis and Bacillus licheniformis to an AW treatment device, we constructed an experimental device including a small grass carp culture pond and three groups of cuboid reactors. The effects of adding the two strains to the AW treatment reactor on the AW purification effect and the microbiota compositions in the AW and packing surface biofilm were analyzed via high-throughput sequencing of the 16S rRNA gene. Our results showed that adding Bacillus bacteria to reactors improved the total nitrogen (TN) removal efficiency and reduced the chemical oxygen demand (COD). Adding both the B. subtillis and B. licheniformis preparations significantly increased the abundance of Firmicutes in the water microbiota of the reactor at the middle and end stages of the experiment. The addition of Bacillus changed the microbiota composition in the water and packing surface biofilm and significantly increased the abundance of Bacillus at the middle and later stages of the experiment. Therefore, the addition of Bacillus improved the TN removal efficiency in the AW grass carp treatment reactors and significantly reduced the COD in the AW by increasing the abundance of Bacillus and changing the microbiota composition in the system. We provide an effective way for improving the purification capacity of biofilm reactor.